KATA SEPAKAT DALAM PERJANJIAN DAN RELEVANSINYA SEBAGAI UPAYA PENCEGAHAN WANPRESTASI - Isdian Anggraeny; Sholahuddin Al-Fatih (Universitas Muhammadiyah Sumatera Utara, 2020)
In a juridical-formal, firmly determined, that each agreement requires the agreement of the parties. However, the implementation of normative tools is not as easy as the textual sounds. Through a juridical approach, writing with the theme